UPAYA MENINGKATKAN HASIL BELAJAR IPA TENTANG MEMBIASAKAN HIDUP SEHAT DENGAN MENGGUNAKAN ALAT PERAGA DAN MENUMBUHKAN SIKAP DISIPLIN PADA MURID KELAS I SD ISLAM NU PUNGKURAN 2016 / 2017 - -, Sulistyoningsih; Karim, Abdul (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This improvement is due to the low learning of Natural Science (IPA) on thesubject matter of healthy environment and unhealthy environment. Moststudents get value under KKM and student discipline attitude method has not been seen yet. Therefore, teachers try to use the image and LCD media to create an interesting and fun learning atmosphere. The purpose of this improvement is to know the improvement of healthy environment and unhealthy environment and the supporting factor of the use of picture and LCD media in science lesson the subject matter of healthy environment and unhealthy environment is considered still less understanding in the students of class I SDI NU PungkuranSemarang Central Subdistrict Semarang Year Lesson 2016 / 2017.Implementation of learning improvement in SDI NU Pungkuran start from 5 October 2016 until 12 October 2016 and consist of 2 cycle (cycle I and cycle II). The results obtained an increase in the percentage of student learning outcomes above the Maximum Exhaustiveness Criteria (KKM), in which the results of completeness cycle I reached 28%, and cycle II reached 98%. Whilethe achievement of the value of discipline character in the second cycle reached 3.5 with the predicate to be consistent. The conclusion of this research is the use of image media can improve the character of discipline and learning achievement of students in science lesson of basic material of healthy environment and unhealthy environment based on environmental condition around in SDI NU Pungkuran Semarang Central Subdistrict Semarang City Lesson 2016/2017.Keywords: image media, learning outcomes, discipline